Laminin-511 and -521 enable efficient in vitro expansion of human corneal endothelial cells - Okumura, Naoki; Kakutani, Kazuya; Numata, Ryohei; Nakahara, Makiko; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; Kinoshita, Shigeru; Koizumi, Noriko (Investigative Ophthalmology & Visual Science, 2015)
The purpose of this study was to investigate the usefulness of laminin isoforms as substrates for culturing human corneal endothelial cells (HCECs) for clinical application of tissue engineering therapy.Expression of specific laminin chains in human corneal endothelium and Descemet's membrane was analyzed at the mRNA and protein levels. The effect of laminin-511 and -521 on cell adhesion and proliferation was evaluated. Recombinant laminin E8 fragments (E8s), which represent functionally minimal forms of laminins, were also evaluated for their effects on cell density and cellular phenotype. The potential involvement of ?3?1 and ?6?1 integrins in laminin signal transduction was also investigated using neutralizing antibodies.Laminin-511 and -521 were expressed in Descemet's membrane and corneal endothelium. These laminin isoforms significantly enhanced the in vitro adhesion and proliferation, and differentiation of HCECs. A cell density of 2200 to 2400 cells/mm2 was achieved when HCECs were cultured on laminin-511 or -521, whereas the density was only 1100 cells/mm2 on an uncoated control. E8s also supported HCEC cultivation with a similar efficacy to that obtained with full-length laminin. Functional blocking of ?3?1 and ?6?1 integrins suppressed the adhesion of HCECs even in the presence of laminin-511.Laminin-511 and -521 were the laminin isoforms present in Descemet's membrane, and these laminins modulate the adhesion and proliferation of CECs. Laminin E8s represent an ideal xeno-free defined substrate for the culture of CECs for clinical applications.
EVALuna2:21243